Psychology diversity towards team interaction processess in Lembaga Zakat Negeri Kedah [LZNK] / Amir Hamzah Abdul Rashid - Abdul Rashid, Amir Hamzah (2019)
Nowadays, team interaction processes is a crucial thing for an organization to have a better quality result to achieve the organizational goals. The purpose of this study is to examine the relationship between independent variables with dependent variable of employees in Lembaga Zakat Negeri Kedah. The items of emotional stability, extraversion, agreeableness and emotional intelligence could possibly affect team interaction processes in Lembaga Zakat Negeri Kedah. The total sample of three populations is 113 after the distribution result. The questionnaire is acceptable and can be regarded as normal distribution through the random sample from Lembaga Zakat Negeri Kedah. This study helps to identify the matter regarding the work as a team among the employees in the organization. The results of hypotheses can identify that there are relationships of four independent variables which are emotional stability ,extraversion, agreeableness and emotional intelligence towards team interaction processes of employees in Lembaga Zakat Negeri Kedah.